Effects of Restricting High Alcohol Content Beverages on Crime in California. (3rd February 2020) - Calvert, Collin; Joshi, Spruha; Erickson, Darin; McKee, Patricia; Toomey, Traci; Nelson, Toben; Jones-Webb, Rhonda
Abstract: Background: Policy restrictions on malt liquor sales have been adopted in several cities throughout the United States in an effort to reduce crime around off-premise alcohol outlets. Although California has implemented the most restrictions on malt liquor sales, no studies in the published literature have evaluated the effects of these policies on reducing crime. Objectives: We evaluated the effectiveness of malt liquor restrictions on reducing crime around off-premise alcohol outlets in six California cities. We hypothesized that adoption of malt liquor policies would be significantly associated with decreases in crime within areas surrounding targeted outlets. Methods: We used an interrupted time-series design with control areas to examine the relationship between malt liquor policies and crime reduction. We compared crime rates three years prior and following adoption of malt liquor policies. Results: Malt liquor policies were associated with modest decreases in crime, largely Part II or less serious crimes such as simple assaults. The effectiveness of malt liquor policies varied by city, with reductions in crime greatest in Sacramento where policies were more restrictive than in other cities. Malt liquor policies were also associated with small increases in nuisance crime, especially in San Francisco. Conclusion: Results suggest that malt liquor policies may have modest effects on reducing crime when they include strong restrictions on the sale of malt liquor products. Results may be informative to other cities considering whether to maintain or change their malt liquor policies as well as cities considering placing restrictions on other high content beverages.